J1 Predictive testing for huntington's disease (HD) in the UK 1994 – 2014: changes in age distribution and outcome of results. (13th September 2016) - Quarrell, Oliver; Baig, Sheharyar; Strong, Mark; Rosser, Elisabeth; Taverner, Nicola; Glew, Ruth; Miedzybrodzka, Zosia; Clarke, Angus; Craufurd, David
Abstract : Introduction: Predictive testing for HD by measurement of the CAG repeat length became available during 1993. A UK HD Predictive Testing Consortium has inter alia collected the number of tests undertaken from 23 UK genetic centres since 1989. Aims: We analysed the age distribution and outcome of results for those presenting for predictive tests in the first full 5-year period (1994–1998) as compared with the last 5 years (2010–2014). In addition, we report on the detection of intermediate and reduced penetrance alleles for the later years of the study. Method: Comparisons were made using the Kolmogorov–Smirnov test for difference in distribution, and the Mann–Whitney test for difference in median. Results: From 1994 to 2014, 8113 predictive tests performed on participants aged ≥18 years and with a prior risk of 50% were recorded in the database. The median age at testing was 37 years with an interquartile range of 29–47 years. There was no significant difference in the median age of participants between the first and last 5-year periods (p = 0.60). Comparison of the age distributions of participants between these two periods showed a statistically significant difference (p < 0.0001), with proportionally more older individuals undertaking the test in the earlier period, and proportionally more younger individuals undertaking the test in the later years. Comparison of the percentage of gene positive results changed from 42% to 49% in these two time periods (p < 0.0001) In the last 5 years of the study period the percentage of intermediate and reduced penetrance alleles was 4.2% and 4.5% respectively. Conclusion: We present data from a large dataset on predictive testing and are able to comment on changes in those presenting for testing over time.